Spectrophotometric Determination of Cefepime and Ezetamibe - Gowri Sankar, D.; Kalyan Sumanth, S.; Pawar, A.K.M.; Madhavi Latha, P.V. (Asian Journal of Chemistry, 2010)
A simple and sensitive visible spectrophotometric method has been developed for the estimation of cefepime and ezetamibe (EZM) in pure as well as in pharmaceutical formulations. This method is based on the formation of oxidative coupling product with 3-methyl-2-benzothiazolinone hydrazone in the presence of ceric ammonium sulphate, which exhibits maximum absorbance at 640 nm and 555 nm for cefepime and ezetamibe respectively. Beer's law is obeyed at the concentration range of 10–40 μg/mL for cefepime and 5–25 μg/mL for ezetamibe. The method has been statistically evaluated and is found to be precise and accurate.